Macroporous interpenetrating network of polyethylene glycol (PEG) and gelatin for cartilage regeneration. (10th June 2016) - Zhang, Jingjing; Wang, Justin; Zhang, Hui; Lin, Jianhao; Ge, Zigang; Zou, Xuenong
Abstract: Poor mechanical properties hinder the application of hydrogels in cartilage tissue engineering. In this study, macroporous interpenetrating network (IPN) hydrogels of gelatin and polyethylene glycol (PEG) were fabricated for use as a functional biomaterial to support chondrocyte culture. The IPN structure enhanced mechanical properties, while the macroporous structure facilitated cell–cell interactions. The hydrogels had pore sizes around 80 μ m with favorable interconnectivity, reduced volume swelling ratios, and nearly unchanged weight swelling ratios with increasing gelatin ratios. More significantly, the Young's modulus increased with increasing gelatin ratio, reaching a 5.3-fold increase ( p   <  0.01) in IPN-10% over that of the PEG group. Chondrocytes developed elongated and fibroblast morphologies with extensive cell–cell interaction throughout IPN hydrogels, compared with round, isolated aggregates in PEG hydrogels. The glycosaminoglycan (GAG) accumulation was significantly higher in IPN hydrogels than in PEG hydrogels at day 21 and day 28. Additionally, significantly higher gene expressions of collagen II ( p   <  0.01) and sox-9 ( p   <  0.01) were found in IPN-10% when compared with other groups. Overall, the macroporous IPN hydrogels showed strong tissue formation abilities and enhanced mechanical properties, demonstrating high potential as scaffolds for cartilage regeneration.